Recent advances in nanomaterial‐assisted detection coupled with capillary and microchip electrophoresis. Issue 3 (22nd November 2020) - Meng, Zhao; Bi, Junmin; Zhang, Qianqian; Ren, Hang; Qin, Weidong
Abstract: Nanomaterials have drawn much attention because of their unique properties enabling them to play important roles in various applications in different areas. This review covers literature data in the Web of Science from January 2017 to August 2020, focusing on the applications of nanomaterials (nanoparticles, quantum dots, nanotubes, and graphene) in CE and MCE to achieve enhanced sensitivity of several detection techniques: fluorescence, colorimetry, amperometry, and chemiluminescence /electrochemiluminescence. For the articles surveyed, the types of nanomaterials used, detection mechanisms, analytical performance, and applications are presented and discussed.